The Dynamics of Adaptation and Innovation of MSMEs in Facing Changes in Consumer Behavior Post Pandemic - Chandra Lukita; Yasir Mustafa Kareem; Bhupesh Rawat (Startupreneur Business Digital (SABDA Journal), 2026)
The COVID-19 pandemic has significantly reshaped consumer behavior, particularly in terms of digital engagement, purchasing preferences, and expectations toward products and services. These changes have compelled Micro, Small, and Medium Enterprises (MSMEs) in Indonesia to adopt adaptive and innovative strategies to sustain their businesses in the post pandemic era. This study aims to explore how Indonesian MSMEs adapt and innovate in response to post pandemic changes in consumer behavior. Using a qualitative research approach, data were collected through in depth interviews and observations involving MSME owners from various sectors, including food and beverage, fashion, and creative industries. The findings reveal that MSMEs implemented innovation not only in product development but also in digital marketing practices, customer relationship management, and technology based distribution channels. Post pandemic consumers were perceived as more health conscious, digitally oriented, and value driven, prompting MSMEs to reconfigure their business models and operational routines. From a theoretical perspective, this study contributes to the literature by demonstrating how Dynamic Capabilities and Innovation Diffusion theories explain MSMEs sustained innovation beyond crisis response, particularly in the post pandemic context of an emerging economy. Practically, the findings offer insights for policymakers and support institutions in designing programs that strengthen digital literacy, managerial flexibility, and innovation capacity among MSMEs to support sustainable post pandemic recovery.